Exploring the contribution of GBAS DFDC in enhancing precision approach - Silva, Weverton da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The Ground-Based Augmentation System (GBAS) is a type of Global Navigation Satellite System (GNSS) augmentation designed to enhance navigation and positioning accuracy and integrity during precision approach and landing operations. Architecture comprises a network of reference stations that generate differential corrections, which are transmitted to the aircraft to improve the aircraft's position. Currently, aviation regulations permit the use of GNSS signals only for the L1 carrier-phase of the GPS or GLONASS. GBAS employs differential GNSS positioning, wherein a significant portion of the systematic errors from satellite signals is mitigated by assuming spatial and temporal correlation between the data of the reference stations and the aircraft. However, in low latitude regions such as Brazil, the higher incidence of ionospheric irregularities leads to significant discrepancies in errors between ground and airborne receivers, as well as degrading signal quality. These conditions can increase positioning errors and degrade performance parameters, making precision approach operations using GBAS unfeasible. The modernization of GNSS, introducing new signals and satellite constellations, is seen as a promising strategy to mitigate or reduce ionospheric effects. Thus, this thesis presents the development of a GBAS Dual-Frequency Dual-Constellation (GBAS DFDC) system for processing, monitoring and evaluating GBAS performance in support of precision approach categories. The aim is to assess whether the performance achieved satisfies the requirements established for specific aviation operations. The implemented system, named GBAS UNESP Experimental Test Bed, is composed of six reference stations from the INCT GNSS-NavAer Network, located in the region of Presidente Prudente, Sao Paulo, Brazil. Four of these stations are configured as ground systems responsible for generating differential corrections and integrity parameters, while the remaining two stations simulate aircraft in static mode, thereby enabling GBAS performance analysis and ionospheric condition monitoring. The system utilizes GNSS data from GPS (L1/L5) and Galileo (E1/E5a), as well as linear combinations of these signals, including pseudorange smoothing, ionosphere-free (IFree), and divergence-free (Divergence Free) combinations. Two MATLAB implementations of GBAS CAT I were developed to support both Single Frequency (SF L1) and IFree modes, incorporating the following functionalities: GNSS data input, pseudorange smoothed via carrier-phase measurements, cycle slip detection, differential correction generation, B-values computation, ionospheric monitoring, aircraft, positioning error, and protection level calculation. GBAS performance was evaluated under both high and low ionospheric scintillation conditions for Single Frequency (SF) L1 and IFree modes. The results demonstrated that, in both ionospheric scenarios and for both simulated aircraft, the SF L1 mode support the CAT I performance requirements over 99% of the analyzed period. In contrast, the IFree mode exhibited reduced availability, achieving CAT I operational conditions for approximately only 90% of the time. The time series analysis of the vertical protection level (VPL) revealed integrity loss events, where VPL values exceeded the 10-meter alert limit. These occurrences were primarily associated with variations in the number of satellites used, which directly influence the VPL magnitude. The exclusion of satellites, resulting from GNSS signal quality monitoring, had a more detrimental impact on the IFree mode than on the SF L1 mode, further underscoring the trade-offs between signal diversity and system robustness in GBAS applications.

O Sistema de Aumento Baseado em Terra (GBAS) é um tipo de sistema de aumento do GNSS projetado para aprimorar a acurácia e a integridade do posicionamento e da navegação durante operações de aproximação e pouso de precisão. Sua arquitetura é composta por uma rede de estações de referência que geram correções diferenciais, as quais são transmitidas à aeronave com o objetivo de melhorar sua estimativa de posição. Atualmente, as regulamentações da aviação permitem o uso de sinais GNSS apenas na portadora L1 do GPS ou do GLONASS. O GBAS usa o posicionamento diferencial GNSS, no qual parte significativa dos erros sistemáticos dos sinais dos satélites é mitigada ao se assumir correlação espaço-temporal dos erros das estações de referência e da aeronave. Entretanto, em regiões de baixa latitude, como o Brasil, a maior incidência de irregularidades ionosféricas resulta em discrepâncias significativas entre os erros observados nos receptores em solo e os da aeronaves, além de degradar a qualidade dos sinais. Essas condições podem aumentar os erros de posicionamento e comprometer os parâmetros de desempenho, tornando inviáveis operações de aproximação de precisão utilizando o GBAS. A modernização dos sistemas GNSS, com a introdução de novos sinais e constelações de satélites, tem sido considerada uma estratégia promissora para mitigar ou reduzir os efeitos ionosféricos. Nesse contexto, esta tese apresenta o desenvolvimento de um sistema GBAS de Dupla Frequência e Dupla Constelação (GBAS DFDC) para o processamento, monitoramento e avaliação do desempenho do GBAS em suporte às categorias de aproximação de precisão. O objetivo é avaliar se o desempenho obtido atende aos requisitos estabelecidos para operações aeronáuticas específicas. O sistema implementado, denominado GBAS UNESP Experimental Test Bed, é composto por seis estações de referência da rede INCT GNSS-NavAer, localizadas na região de Presidente Prudente, São Paulo, Brasil. Quatro dessas estações são configuradas como sistemas em solo responsáveis pela geração de correções diferenciais e parâmetros de integridade, enquanto as duas restantes simulam aeronaves em modo estático, permitindo a análise do desempenho do GBAS e o monitoramento das condições ionosféricas. O sistema utiliza dados GNSS provenientes do GPS (L1/L5) e do Galileo (E1/E5a), bem como combinações lineares desses sinais, incluindo suavização de pseudodistância, combinações livres da ionosfera (IFree) e livres de divergência (Divergence Free). Foram desenvolvidas duas implementações em MATLAB do GBAS CAT I, capazes de operar tanto no modo de frequência única (SF L1) quanto no modo IFree, incorporando as seguintes funcionalidades: entrada de dados GNSS, suavização da pseudodistância via medições de fase da portadora, detecção de cycle slips, geração de correções diferenciais, cálculo dos B-values, monitoramento ionosférico, posicionamento da aeronave, cálculo do erro de posicionamento e dos níveis de proteção. O desempenho do GBAS foi avaliado sob condições de alta e baixa cintilação ionosférica para os modos SF L1 e IFree. Os resultados demonstraram que, em ambos os cenários ionosféricos e para ambas as aeronaves simuladas, o modo SF L1 atende aos requisitos de desempenho para CAT I em mais de 99% do período analisado. Em contraste, o modo IFree apresentou menor disponibilidade, atingindo condições operacionais de CAT I em aproximadamente 90% do tempo. A análise das séries temporais do nível de proteção vertical (VPL) evidenciou eventos de perda de integridade, nos quais os valores de VPL excederam o limite de alerta de 10 metros. Essas ocorrências estiveram principalmente associadas a variações no número de satélites utilizados, que influenciam diretamente a magnitude do VPL. A exclusão de satélites, decorrente do monitoramento da qualidade dos sinais GNSS, impactou de forma mais significativa o modo IFree do que o modo SF L1, evidenciando os compromissos existentes entre diversidade de sinais e robustez do sistema em aplicações GBAS.
Explorando a contribuição de GBAS DFDC na aproximação de precisão
Keywords: Precision approach; Differential corrections; Protections levels; Ionospheric gradient; Performance requirements; Aproximação de precisão; Correções diferenciais; Níveis de proteção; Gradiente ionosférico; Requisitos de desempenho